Pre-growout and growout experiences with white seabream (Diplodus sargus sargus, Linnaeus, 1758) and sharpsnout seabream (Diplodus puntazzo, Cetti, 1977) - Abellán E.; García-Alcázar A. (Marine aquaculture finfish species diversification, 1995)
Bream species offer good prospects for new fish culture in the Mediterranean. The aim of this work was to evaluate the possibility of rearing white seabream (Diplodus sargus sargus) and sharpsnout seabream (Puntazzo puntazzo) in pre-growout and growout phases. Results were compared with those of gilthead seabream (Sparus aurata). The growth of the white seabream, reaching 58.03 plus minus 19.24 g of average weight and 13.54 plus minus 1.75 cm of average length (mean plus minus standard deviation; n equal to 40) in 13 months, renders this species not very appropriate for intensive aquaculture. On the other hand, the sharpsnout seabream showed better results, reaching 121.99 plus minus 38.21 g and 18.24 plus minus 1.83 cm (mean plus minus standard deviation; n equal to 40) by the 13th month. The survival rate at the end of pre-growout was 84.1 per cent, and food conversion less than 2. Poor global results of survival (47.6 per cent) and food conversion (approximately 5) could be improved by adapting food characteristics and culture techniques to this species.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)